Effect of soy protein isolate on the thermal, mechanical and morphological properties of poly (ε-caprolactone) and corn starch blends - Mariani, P. D.S.C.; Allganer, K.; Oliveira, F. B.; Cardoso, E. J.B.N. [UNESP]; Innocentini-Mei, L. H. (Elsevier, 2009)
The development of biodegradable polymers is considered to be a good alternative to decrease the volume of the plastic waste disposed into the environment every year. The use of natural polymers as raw materials to develop polymer blends and composites has increased the demand for renewable sources such as starch and soy protein. In this work, the authors prepared and characterized the thermal, mechanical and morphological properties of blends based on poly (ε-caprolactone) and modified corn starch, with added soy protein isolate (SPI) and sorbitol. All samples were processed by extrusion in a single-screw extruder and hot pressing. It was observed that the addition of modified corn starch and SPI were responsible for the reduction of thermal and mechanical properties of the materials, compared to pristine PCL. However, with increasing amounts of SPI and the reduction of starch incorporated into the samples, their properties tend to recover. The insertion of soy protein isolate in the formulations was done with the aim of balancing the C/N ratio of the blend, which plays a key role in the biodegradation process of these materials. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Characterization; Poly(ε-caprolactone); Soy protein; Starch